Tectonic and basinal evolution of the Outer Carpathians based on example of geological structure of the Grabownica, Strachocina and Łodyna hydrocarbon deposits - JANKOWSKI, Leszek; PROBULSKI, Jaromir (Geology, Geophysics and Environment, 2011)
Łodyna, Grabownica, Strachocina, Wańkowa and Leszczowate oil fields are situated in the northern margin of the central Carpathian Depression, on both sides of so called Węglówka Unit and it’s prolongation to the East. Fieldwork and seismic section interpretations indicate multistage and complexity of process of closing basin and tectonic deformation. During the compression and oblique collision stage of the tectonic deformation southern margin of Węglówka horst was reactivated as a strike-slip fault and associated (with this strike-slip) flower structures were developed. The Węglówka intrabasinal ridge (horst) was cut in many places off and a few tectonic elements has been created. In front of the Silesian Unit thrust a footwall shortening is visible. The whole area of these oil fields is apparently connected with reactivated tectonic zone, southern margin of formerly intrabasinal Węglówka ridge. In the last stage of deformation some thrust and strike-slip structures were reactivated as a normal faults (posttectonic collapse structures). Immaturity of the Menilite Beds in this region suggests a lack of relationship between the local oil and Menilite Beds and indicates migration origin of local oil. A lots of tectonic mélange zones developed in this area play important role in petroleum system creating open or closed geochemical system - in some cases they are migration paths for gas and oil. However, main migration paths in this seems to be deep rooted, reactivated, normal faults normal to the strike of main tectonic elements, probably inherited from syncollisional extension stage.